Solar-Wind Structures That Are Not Destroyed by the Action of Solar-Wind Turbulence - Borovsky, Joseph E. (Frontiers in Astronomy and Space Sciences, 2021)
If MHD turbulence is a dominant process acting in the solar wind between the Sun and 1 AU, then the destruction and regeneration of structure in the solar-wind plasma is expected. Six types of solar-wind structure at 1 AU that are not destroyed by turbulence are examined: 1) corotating-interaction-region stream interfaces, 2) periodic density structures, 3) magnetic structure anisotropy, 4) ion-composition boundaries and their co-located current sheets, 5) strahl-intensity boundaries and their co-located current sheets, and 6) non-evolving Alfvénic magnetic structure. Implications for the solar wind and for turbulence in the solar wind are highlighted and a call for critical future solar-wind measurements is given.